The Influence Of Traditional Games On Manipulativ Motion Skills In Students Of Muhammadiyah Nganjuk Elementary School - Hamid, Faisol; Desranto, Akhmad Fendi (PHEDHERAL, 2022)
Physical education and sports are a long-term investment in efforts to foster the quality of Indonesian human resources. The development of motion in childhood is very prominent, especially in locomotor, non-locomotor and manipulative abilities. Children perform various basic movements perfectly such as running, jumping, pushing, throwing and others. Improvement or improvement of basic movements occur in childhood. Therefore, alternatives the solution is with game and sport activities. Traditional games boi-boian, baseball, and maccuke contain physical movements or activities, through traditional games in addition to teaching physical movements such as running, jumping, throwing and hitting but also teach sportsmanship and cooperation.This study aims to determine the effect of traditional games on the manipulative motion of students of SD Muhammadiyah Nganjuk in the realm of manipulative movement skills. This research is an experimental research, with a quantitative approach, the Pre experiment design method uses the One Group Pretest-Posttest Design model. The sampling technique uses the cluster method. The sample in this study was 30 students in grade IV at SD Muhammadiyah Nganjuk. Data collection methods in this study used a tennis ball throwing test. This study uses paired sample t-test analysis techniques at a significance level of 0.05 with the help of a computer program SPSS 20.0 for windows. Hypothesis testing is if (Ho) is rejected Sig (2-tailed) <0.05.Analysis results Based on the results of the data analysis above, it can be concluded that the SPSS calculation states that the Sig. (2-tailed)> α obtained by 0.052 and the value of α = 0.05, means 0.052> 0.05. With the results of the calculation of T-count of 20.637 and T table of 1.311. So 20,637> 1,311 so that it can be concluded there is the influence of traditional games on manipulative motion skills in students of SD Muhammadiyah Nganjuk.